Efficient organic pollutant mineralization via PMS-sonophotocatalysis with doped-ZnO-CNT aerogels - Queralt Bautista; Majdi Benamara; Shanyu Zhao; Elvira Gómez; Albert Serrà (Applied Catalysis O: Open)
This study investigates some characteristics of multi-walled carbon nanotube (MWCNT)-integrated zinc oxide (ZnO)-based aerogels doped with aluminum (A4ZO), gallium (G5ZO), and indium (I1ZO). The objective of this study is to enhance the removal of pollutants in environmental remediation. The morphology attributes of the aerogel were found to significantly influenced by the inclusion of dopants. Differences in particle aggregation and dispersion were observed in the scanning electron microscopy (SEM) images. X-ray diffraction (XRD) revealed that the hexagonal wurtzite structure of ZnO remained throughout all the samples, and Brunauer–Emmett–Teller (BET) analysis showed that their mesoporous nature and surface areas were enlarged. Photoluminescence (PL) spectra and Fourier-transform infrared (FTIR) spectroscopy displayed how dopants changed the defect density and optical properties of ZnO. Furthermore, under the combined effect of visible light, sonication, and peroxymonosulfate (PMS) activation, the I1ZO-CNT aerogel exhibited notable efficacy in degrading tetracycline, with a degradation efficiency of 97.6 %. The enhanced efficiency of the I1ZO-CNT aerogel was attributed to three factors: effective light harvesting, high charge transfer efficiency, and robust reactive oxygen species (ROS) generation. Furthermore, the stability of the doped ZnO-CNT aerogel was demonstrated by reusability tests, which revealed minimal leaching of dopants. These findings underscore the promise of doped ZnO-CNT aerogels in sustainable wastewater treatment applications.